2005
DOI: 10.1089/fpd.2005.2.70
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Risk Factors for Escherichia coli O157 in Market-Ready Beef Cattle from 12 U.S. Feedlots

Abstract: Determination of Escherichia coli O157 prevalence immediately prior to shipment and harvest is an important facet of the ecology of this organism, which requires further elucidation. As part of a larger study to measure the effects of within-pen prevalence of E. coli O157 on subsequent carcass contamination, fecal samples from 15 pens of cattle in each of 12 different feedlots in three states (Colorado, Nebraska, and Montana) were collected from June through September 2002. Thirty fresh fecal samples were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 12 publications
1
34
1
Order By: Relevance
“…Dewell et al (2005) were one of the first research groups that found feeding DGS as a risk factor for E. coli O157:H7 carriage in a beef cattle longitudinal study. Two studies using naturally infected feedlot cattle ( Jacob et al, 2008c) and experimentally infected Holstein calves ( Jacob et al, 2008a) reported higher prevalence of E. coli O157 when DGS was included in the diet.…”
Section: Discussionmentioning
confidence: 99%
“…Dewell et al (2005) were one of the first research groups that found feeding DGS as a risk factor for E. coli O157:H7 carriage in a beef cattle longitudinal study. Two studies using naturally infected feedlot cattle ( Jacob et al, 2008c) and experimentally infected Holstein calves ( Jacob et al, 2008a) reported higher prevalence of E. coli O157 when DGS was included in the diet.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a multistate epidemiologic study conducted in feedlots showed that the odds of obtaining an E. coli O157-positive fecal sample were six times higher if cattle were fed brewers' grains, a fermentative product similar to DG (9). The authors suggested that the increased odds of obtaining an E. coli O157-positive sample may have been due to components of the brewers' grain or management factors associated with brewers' grain …”
Section: Discussionmentioning
confidence: 99%
“…The absence of starch and the presence of relatively high concentrations of ruminal escape protein and bran (fiber) components of DG are likely to impact the ecology of the hindgut. Dewell et al (9) found that fecal samples from cattle fed brewers' grains, a fermentative product similar to DG, were more likely to be positive for E. coli O157 than fecal samples from cattle not fed brewers' grains. In a previous study (25), we observed that feedlot cattle fed WDG had a higher prevalence of E. coli O157 on one of two collection days; however, the positive association was apparent on both days.…”
mentioning
confidence: 99%
“…Regional differences in the probability for cattle to shed E. coli O157:H7 have been reported (Dewell et al, 2005). Also, regional differences were reported in a study that evaluated the probability to detect E. coli O157:H7 in two large beef processing plants, one located in the southern United Sates and the other in the northern United States (Rivera-Betancourt et al, 2004).…”
Section: Discussionmentioning
confidence: 98%